Presentation of the structure of industry divisions of the websites of national libraries on the example of veterinary sciences - Halytska, Svitlana (Bìblìotečnij vìsnik, 2024)
The purpose of the study is research and analysis of the presentation of veterinary sciences on the websites of national libraries, substantiation of the importance of structuring rubrics according to the features of the thematic filling of the funds of a certain library to improve navigation and search by library hierarchy. The research methodology is based on the use of general scientific and special research methods (generalization, systematic, classification, descriptive). Scientific novelty. The article examines the issue of the formation of the structure of the "Veterinary" section by the national libraries of the world according to different classification systems. The importance of providing access to the structure and using classification indexes as search elements during a thematic search is indicated. Examples of the use of the Universal Decimal Classification, Decimal Classification of M. Dewey, Classification of the Library of Congress of the USA, as well as the NBUV Rubricator for the construction of detailed rubrics of the section of veterinary sciences are given. It is emphasized that specifying indexes of various classifications in the bibliographic records of documents creates conditions for the integration of libraries into the common information space. Conclusions. The use of library classifications in the organization of the funds of the national libraries of the world and the deepening of the extensive system of correspondence between independent classification schemes significantly facilitate the processes of scientific processing of documents, in particular, parallel indexing of receipts according to different classifications, and thematic search in electronic catalogs, guarantee effective access to document arrays and obtaining relevant responses to user requests, i. e. determine the high quality of information and search systems of the national libraries of the world.